Krodha Krura Tokoh Bathari Durga Wayang Purwa - Andi Wicaksono (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2021)
This article discusses the meaning of the Rakessi form of the figure Bathari Durga in the wayang kulit purwa. The discussion uses Paul Ricoeur’s hermeneutic meaning analysis which emphasizes the terminology aspect. The meaning analysis is carried out by reading through the events of the character Bathari Durga in several texts of lakon in the wayang kulit purwa play, then analyzing the existence of the terminology aspects of ‘raksasa’, ‘raksesi’, ‘buta’ and ‘diyu’ with other phenomena in the text of lakon. The results of the analysis show that the form of raksesi does not mean the same as the understanding of low-level creatures, cruel, and filled with dark traits. The divine capacity as the main goddess is still visible in the text of lakon in wayang purwa with the capacity as isthadewata, so that her personal capacity is still at a high level. The form of raksesi with the name Durga with the title ‘bathari’ represent a blend of aspects ‘krodha’ and ‘krura’ in the style of worshiping ‘sakti’ in the form of ‘Bhairawi Shiva’.